Healthcare workers' attitudes toward and factors influencing their acceptance of an annual COVID-19 booster vaccine: a cross-sectional study in Palestine - Beesan Maraqa; Zaher Nazzal; Hassan Baroud; Mahmoud Douden; Yousef El Hamshary; Tala Jalamneh (BMC, 2024)
Abstract Background The emergence of several SARS-CoV-2 variants may necessitate an annual COVID-19 booster vaccine. This study aimed to evaluate healthcare workers' (HCWs) acceptance of a COVID-19 yearly booster vaccine if recommended and its association with their attitudes and burnout levels. Methods We used an online self-administered questionnaire to conduct a cross-sectional study of all HCWs in the West Bank and Gaza Strip of Palestine between August and September 2022. We used the Vaccination Attitudes Examination scale to assess HCWs' vaccination attitudes and the Maslach Burnout Inventory to assess work-related Burnout. In addition, we conducted logistic regression to identify factors independently associated with the acceptance of the booster vaccine. Results The study included 919 HCWs; 52.4% were male, 46.5% were physicians, 30.0% were nurses, and 63.1% worked in hospitals. One-third of HCWs (95% CI: 30.5%-36.7%) said they would accept an annual COVID-19 booster vaccine if recommended. HCWs who are suspicious of vaccine benefits [aOR = .70; 95%CI: .65-.75] and those concerned about unforeseeable future effects [aOR = .90; 95%CI: .84-.95] are less likely to accept the booster vaccine if recommended, whereas those who receive annual influenza vaccine are more likely to get it [aOR = 2.9; 95%CI: 1.7-5.0]. Conclusion Only about a third of HCWs would agree to receive an annual COVID-19 booster vaccine if recommended. Mistrust of the vaccine's efficacy and concerns about side effects continue to drive COVID-19 vaccine reluctance. Health officials need to address HCWs' concerns to increase their acceptance of the annual vaccine if it is to be recommended.